Weak investor protection of Chinese state-controlled listed companies: a theory of governmental intervention. (1st January 2014) - Zhang, Lin
Confronted with the torrent of corporate scandals, legal scholars have already contributed abundant intellectual products on improving the investor protection of Chinese state-controlled listed companies. However, the majority of these contributions focus on the refinement of relevant legal institutions of investor protection in Chinese law or the transplantation of new ones from major commercial jurisdictions. Few of them pay attention to the link between governmental intervention and the malfunction of existing investor-oriented mechanisms of the Chinese legal system. This article demonstrates that apart from legal defects, governmental intervention which disrupts the function of investor-friendly legal institutions in place is another non-negligible factor, or even the most fundamental one in the context of China, to explain the weak investor protection of Chinese state-controlled listed companies. Therefore, in order to improve investor protection of Chinese state-controlled listed companies, the political reform on the establishment of a public servant government which has been underway in China must be continued.